2009
DOI: 10.1038/onc.2009.147
|View full text |Cite
|
Sign up to set email alerts
|

SirT1-null mice develop tumors at normal rates but are poorly protected by resveratrol

Abstract: The function of the class III histone deacetylase, Sir2, in promoting lifespan extension is well established in small model organisms. By analogy, SirT1, the mammalian orthologue of Sir2, is a candidate gene to slow down aging and forestall the onset of age-associated diseases. We have used SirT1-null mice to study the function of SirT1 in susceptibility to tumorigenesis. The number of intestinal polyps induced in mice carrying the Apc min mutation was unaffected by the SirT1 genotype although the average poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 59 publications
10
113
0
Order By: Relevance
“…21 However, no notable tumor formation has been reported in 2 aging studies using SIRT1 Ϫ/Ϫ mice over 18-24 months 48,49 and SIRT1 homozygous knockout does not increase intestinal polyp load in Apc min/ϩ mice. 50 Given the results of the present study, it is likely that tissue types may influence SIRT1 functions in cancer. Nevertheless, our study reveals SIRT1 activation as a novel mechanism for CML cell proliferation and survival, …”
Section: Discussionmentioning
confidence: 76%
“…21 However, no notable tumor formation has been reported in 2 aging studies using SIRT1 Ϫ/Ϫ mice over 18-24 months 48,49 and SIRT1 homozygous knockout does not increase intestinal polyp load in Apc min/ϩ mice. 50 Given the results of the present study, it is likely that tissue types may influence SIRT1 functions in cancer. Nevertheless, our study reveals SIRT1 activation as a novel mechanism for CML cell proliferation and survival, …”
Section: Discussionmentioning
confidence: 76%
“…First, SIRT1 overexpression is shown to suppress intestinal polyp formation in Apc min/ þ mice (Firestein et al, 2008), Nicotinamide phosphoribosyltransferase and prostate cancer B Wang et al suggesting a tumor suppressor function. In contrast, the SIRT1 homozygous knockout fails to increase intestinal polyp load in Apc min/ þ mice (Boily et al, 2009). Second, Oberdoerffer et al (2008) show that SIRT1 overexpression or resveratrol treatment reduces thymic lymphoma in p53 þ /À background.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also suggest that SIRT1 is a haploinsufficient tumor suppressor (Wang et al, 2008). However, no notable tumor formation has been reported in two aging studies using SIRT1 À/À mice over 18 to 24 months (Boily et al, 2008;Li et al, 2008) and SIRT1 homozygous knockout does not increase intestinal tumors in Apc min/ þ mice (Boily et al, 2009). Therefore, more in vivo studies are needed for comprehensive understanding of roles of SIRT1 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of SIRT1 in murine intestines reduces the incidence of cancer and growth in a mouse colon cancer model: SIRT1 was shown to deacetylate -catenin and inhibit its accumulation in the nucleus, which lead to the hyperactivation of -catenin and the formation of tumors (Firestein et al, 2008). Another study showed that the SIRT1 activator resveratrol also protects mice that are heterozygous for p53 from cancer (Boily et al, 2009;Oberdoerffer et al, 2008). Consistent with these results, it was shown that SIRT1 haploinsufficiency facilitates tumorigenesis in these mice by accelerating tumorigenesis (Wang et al, 2008).…”
Section: Roles In Cancermentioning
confidence: 99%